Another Emerging Mosquito-Borne Disease? Endemic Ross River Virus Transmission in the Absence of Marsupial Reservoirs. (7th March 2018) - Flies, Emily J; Lau, Colleen L; Carver, Scott; Weinstein, Philip
Abstract: Ross River virus (RRV) is endemic to Australia and Papua New Guinea, with marsupials (especially macropods) as the primary reservoir hosts. Its geographic range was thought to be limited by the distribution of reservoir hosts, but recent evidence suggests that the virus can circulate endemically in the Pacific Islands, where marsupials are absent. RRV therefore has the potential for wider emergence because mammalian diversity in the Pacific Islands is limited and the possible species that have been sustaining endemic transmission are panglobal in distribution. Furthermore, RRV is a vector generalist and can be transmitted by numerous mosquito species, including Culex and the globally invasive Aedes aegypti and Ae. albopictus. We review the evidence for RRV expanding its host and geographic range from prehistoric times to the present and for it to potentially pose a threat as another emerging arbovirus with significant implications for human health far beyond its currently known endemic range.